Exploring the Role of Emotional Intelligence Training in Enhancing Teacher-Student Relationships and Academic Performance - Pattiasina, Petrus Jacob; Zamakhsari, Ahmad; Halim, Chandra (International Education Trend Issues, 2024)
This study explores the impact of emotional intelligence (EI) training on enhancing teacher-student relationships and improving academic performance in middle schools. Using a quasi-experimental design, the research involved 60 teachers and 600 students, with the teachers randomly assigned to either an intervention group, which received EI training, or a control group. Quantitative measures included the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT), the Teacher-Student Relationship Inventory (TSRI), and academic performance assessments through grades and standardized test scores. Qualitative data were collected via semi-structured interviews and focus groups. The results indicated significant improvements in teachers' EI levels, better teacher-student relationships, and higher academic performance among students in the intervention group. Qualitative findings corroborated these outcomes, highlighting enhanced communication and classroom climate. These findings underscore the potential benefits of integrating EI training into teacher professional development programs to foster both emotional well-being and academic success among students.